On-Line Fabric Disk Sorptive Extraction via a Flow Preconcentration Platform Coupled with Atomic Absorption Spectrometry for the Determination of Essential and Toxic Elements in Biological Samples - Viktoria Kazantzi; Victoria Samanidou; Abuzar Kabir; Kenneth G. Furton; Aristidis Anthemidis (Separations, 2018)
Fabric phase sorptive extraction (FPSE) has gained notable attention and interest both in batch and automatic mode utilizing advanced sol-gel derived microextraction sorbents and the hydrophobic/hydrophilic properties of fabric substrates. Recently, the innovative on-line fabric disk sorptive extraction (FDSE) has opened new opportunities in the field of automatic sample preparation (preconcentration/separation). A novel sol-gel sorbent based on caprolactone-dimethylsiloxane-caprolactone block polymer comprised of a non-polar dimethylsiloxane and hydrophilic caprolactone as a coating on hydrophobic polyester fabric substrate and its evaluation in an automatic FDSE system coupled with flame atomic absorption spectrometry (FAAS), is presented for the first time. The capabilities of the proposed flow injection system were assessed for trace Cu(II), Ni(II), Zn(II), Pb(II), and Cd(II) determination in urine samples. The method was based on the on-line formation of target analytes with ammonium pyrrolidine dithiocarbamate (APDC) and their retention onto the surface of the fabric disk medium. Methyl isobutyl ketone (MIBK) was used to elute metal–APDC complexes directly into the nebulizer-burner system of FAAS. For 90 s of preconcentration time, enhancement factors of 250, 130, 185, and 36 and detection limits (3 s) of 0.15, 0.41, 1.62, and 0.49 μg L−1 were obtained for Cu(II), Ni(II), Pb(II), and Cd(II), respectively. For 30 s of preconcentration time, an enhancement factor of 49 and a detection limit of 0.12 μg L−1 was achieved for Zn(II) determination. The precision, expressed as relative standard deviation (RSD), was lower than 3.5% for all metals. The accuracy of the proposed method was sufficient and evaluated by analyzing certified reference materials and biological samples.